Method for producing reduction catalyst precursor

A novel method using alkali carbonate and sulfate ions in the neutralization of nickel and zirconium compounds addresses the cost and NOx issues of rare earth-stabilized catalysts, producing a highly active and stable reduction catalyst precursor for methanation.

JP2024177042AInactive Publication Date: 2024-12-19SAKAI CHEM IND CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023215606
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-07
Filing Date
2023-12-21
Publication Date
2024-12-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for producing reduction catalysts using rare earth elements as stabilizers are costly due to uneven global distribution and generate significant NOx emissions during calcination, necessitating a method that avoids these issues while maintaining high activity.

Method used

A method involving a neutralization reaction of nickel-containing and zirconium-containing compounds with alkali carbonate in the presence of sulfate ions, followed by filtration, washing, and heat-treatment to produce a reduction catalyst precursor without rare earth elements and minimal NOx generation.

Benefits of technology

The method produces a highly active reduction catalyst precursor with reduced NOx emissions during calcination, suitable for methanation catalysts, exhibiting improved catalytic activity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177042000001
    Figure 2024177042000001
  • Figure 2024177042000002
    Figure 2024177042000002
  • Figure 2024177042000003
    Figure 2024177042000003
Patent Text Reader

Abstract

To provide a method for producing a reduction catalyst precursor that exhibits high activity without using a stabilizing agent, such as a rare earth element, and without generating a large amount of NOx during calcination.SOLUTION: A method for producing a reduction catalyst material includes: a neutralization step of neutralizing a nickel-containing compound, a zirconium-containing compound, and an alkali carbonate in the presence of a sulfate ion; a step of filtering and water-washing the product obtained in the neutralization step to remove a water-soluble component; and a step of heat-treating the product after the removal step. The content of Na2O in the oxide obtained by the heat treatment step is 1.0 mass% or less, and the content of SO3 is 0.5 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a reduced catalyst precursor. More specifically, the present invention relates to a method for producing a reduced catalyst precursor useful for methanation catalysts and the like. [Background technology]

[0002] In recent years, global warming has become a serious social issue, and efforts to achieve decarbonization by reducing carbon dioxide emissions, which are said to be one of the causes of global warming, are becoming more and more common. As one of the measures, various methods for carbon recycling, which converts carbon dioxide into valuable materials, have been considered, and among them, methanation, which reduces carbon dioxide with hydrogen to obtain methane, is a promising method and demonstration tests are being conducted around the world. As a catalyst for reducing carbon dioxide with hydrogen to produce methanation (methanation catalyst), a catalyst containing tetragonal zirconia stabilized with a rare earth such as yttrium or lanthanum and nickel is known to be effective.

[0003] Regarding reduction catalysts containing tetragonal zirconia and nickel, Patent Documents 1 and 2 disclose catalysts in which Ni or Co is supported on a tetragonal zirconia-based carrier stabilized with a rare earth element. Furthermore, Patent Document 3 discloses a technique in which the surface of particles of at least one metal selected from the iron-group transition elements (Ni, Fe, Co) is coated with a mixed oxide of zirconium oxide and an oxide of at least one metal selected from the group consisting of cerium, lanthanum, and barium. Furthermore, Patent Document 4 discloses a technique for stabilizing the tetragonal crystal structure by incorporating Ca and Ni into the crystal structure of zirconia. Patent Document 5 discloses a technique for stabilizing the tetragonal and / or cubic crystal structure of zirconia by using at least one transition element selected from the group consisting of Mn, Fe, and Co as a stabilizing element. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-254508 A [Patent Document 2] JP 2009-034650 A [Patent Document 3] JP 2009-034654 A [Patent Document 4] International Publication No. 2016 / 013488 [Patent Document 5] JP 2018-020278 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, various reduction catalysts have been developed in the past. However, in the method of using a stabilizer such as a rare earth element to obtain tetragonal zirconia, rare earth elements are expensive, and the ores are produced in a limited number of countries, which causes problems in terms of cost and stable supply. In addition, in the method of using nitrates as metal salts and calcining them, a large amount of NOx is generated during calcination, which requires a calcination furnace equipped with a denitrification facility. Therefore, there has been a demand for a method of producing a reduction catalyst that exhibits high activity without using a stabilizer such as a rare earth element and without generating a large amount of NOx during calcination.

[0006] The present invention has been made in consideration of the above-mentioned current situation, and has an object to provide a method for producing a precursor of a reduction catalyst that exhibits high activity without using a stabilizer such as a rare earth element and without generating a large amount of NOx during calcination. [Means for solving the problem]

[0007] The present inventors have conducted various studies on methods for producing reduction catalyst materials, and have found that by neutralizing a nickel-containing compound and a zirconium-containing compound with an alkali carbonate in the presence of sulfate ions, filtering and washing the product obtained by the neutralization reaction to remove water-soluble components, and heat-treating the product obtained, the contents of Na2O and SO3 in the obtained oxide are reduced to predetermined amounts or less, and it is possible to produce a precursor of a reduction catalyst exhibiting high activity without using a stabilizer such as a rare earth element and without generating a large amount of NOx during firing. The inventors have thus come up with the idea of ​​brilliantly solving the above-mentioned problems, and have arrived at the present invention.

[0008] The present invention includes the following method for producing a reduced catalyst precursor, etc. [1] A method for producing a reduction catalyst precursor, the method comprising: a neutralization step of neutralizing a nickel-containing compound and a zirconium-containing compound with an alkali carbonate in the presence of sulfate ions; a step of filtering and washing the product obtained in the neutralization step to remove water-soluble components; and a step of heat-treating the product after the removal step, wherein the oxide obtained by the heat treatment step has a NaO content of 1.0 mass% or less and a SO content of 0.5 mass% or less. [2] The method for producing a reduction catalyst precursor according to the above [1], wherein in the neutralization step, an aqueous solution containing a nickel-containing compound and a zirconium-containing compound is mixed with an aqueous solution of an alkali carbonate. [3] The method for producing a reduction catalyst precursor according to the above [1] or [2], wherein a silicon-containing compound is further added in the neutralization step. [4] The method for producing a reduction catalyst precursor according to the above [3], wherein the amount of the silicon-containing compound added, calculated as SiO2, is 0.5 to 15 mass% relative to 100 mass% in total of nickel element and zirconium element. [5] The method for producing a reduction catalyst precursor according to any one of the above [1] to [4], wherein the above alkali carbonate is sodium carbonate and / or sodium hydrogen carbonate. [6] The method for producing a reduction catalyst precursor according to any one of the above [1] to [5], wherein the pH during the neutralization reaction in the neutralization step is 6.5 to 8.5. [7] The method for producing a reduction catalyst precursor according to any one of the above [1] to [6], wherein the reaction temperature in the neutralization step is 50° C. or higher. [8] A method for producing a reduction catalyst precursor according to any one of the above [1] to [7], comprising the neutralization step, the water-soluble component removing step, and the heat treatment step, and further comprising a step of reducing an oxide obtained by the heat treatment step, wherein the oxide obtained by the heat treatment step has a NaO content of 1.0 mass% or less and a SO content of 0.5 mass% or less. [9] A method for producing the reduction catalyst according to [8] above, comprising a step of oxidizing the surface of the product obtained in the reduction step.

[10] The method for producing a reduction catalyst according to [8] or [9] above, wherein the reduction catalyst is a methanation catalyst.

[11] A reduction catalyst precursor containing nickel oxide and zirconium oxide, the reduction catalyst precursor having a monoclinic zirconium oxide ratio of 20 volume % or less relative to 100 volume % of zirconium oxide, and having a CO adsorption amount of 3 cm3 after reduction treatment under the following conditions: 3 / g or more of reduced catalyst precursor. <Reduction treatment conditions> Amount of reduction catalyst precursor: 0.04g Gas type and flow rate: Hydrogen 50mL / min Temperature: 400℃ Reduction processing time: 30 minutes

[12] The reduction catalyst precursor according to

[11] above, further comprising a silicon-containing compound.

[13] The reduction catalyst precursor according to

[11] above, wherein the content ratio of the silicon-containing compound calculated as SiO2 is 0.5 to 15 mass% relative to 100 mass% of the total of nickel element and zirconium element in the reduction catalyst precursor.

[14] The specific surface area is 30 m 2 / g or more.

[15] A reduction catalyst which is a reduction product of the reduction catalyst precursor according to any one of

[11] to

[14] above.

[16] The reduction catalyst according to

[15] above, which is a methanation catalyst.

[17] A method for producing methane, comprising a step of reducing carbon dioxide using the reduction catalyst according to

[15] or

[16] above. Effect of the Invention

[0009] The method for producing a reduction catalyst precursor of the present invention has the above-mentioned configuration and can produce a precursor of a reduction catalyst that exhibits high activity without using a stabilizer such as a rare earth element and without generating a large amount of NOx during calcination, and therefore can be suitably used for producing reduction catalysts such as methanation catalysts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The preferred embodiments of the present invention are specifically described below, but the present invention is not limited to the following description, and can be modified as appropriate within the scope of the present invention. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below also falls within the preferred embodiments of the present invention.

[0011] 1. Method for producing reduced catalyst precursor The method for producing a reduction catalyst precursor of the present invention includes a neutralization step of neutralizing a nickel-containing compound and a zirconium-containing compound with an alkali carbonate in the presence of sulfate ions, a step of filtering and washing the product obtained in the neutralization step with water to remove water-soluble components, and a step of heat-treating the product after the removal step. In the method for producing a reduction catalyst precursor of the present invention, the neutralization step is carried out, whereby a reduction catalyst precursor can be produced without using a stabilizer such as a rare earth element and without generating a large amount of NOx during calcination. Furthermore, by using an alkali carbonate in the neutralization step, nickel is precipitated as basic nickel carbonate during neutralization, and by heating this in the heat treatment step, carbonic acid in the basic nickel carbonate is removed, thereby ensuring a sufficient pore volume of the reduction catalyst obtained. In addition, by including the above-mentioned specific steps in the manufacturing method of the reduced catalyst precursor, the oxide obtained by the heat treatment step has a Na2O content of 1.0 mass% or less and a SO3 content of 0.5 mass% or less, which allows the obtained reduced catalyst to exhibit better catalytic activity.

[0012] The method for producing a reduced catalyst precursor of the present invention includes a neutralization step of neutralizing a nickel-containing compound and a zirconium-containing compound with an alkali carbonate in the presence of sulfate ions. In the method of firing using an acidic zirconia sol, acidic gases such as NOx are generated, which cause corrosion of equipment. However, by neutralizing the nickel-containing compound and the zirconium-containing compound, the corrosion of the equipment can be sufficiently suppressed. The neutralization step is not particularly limited as long as it causes a neutralization reaction between the nickel-containing compound and the zirconium-containing compound and the alkali carbonate. These compounds may be added as solids to one container and mixed in a solvent, or solutions of each compound may be prepared and then the solutions may be mixed. A preferred form is mixing a solution containing a nickel-containing compound and a zirconium-containing compound with a solution containing an alkali carbonate.

[0013] The solvent may be any solvent capable of dissolving the compound, and is preferably water. In the neutralization step, the embodiment in which an aqueous solution containing a nickel-containing compound and a zirconium-containing compound (hereinafter also referred to as aqueous solution (A)) is mixed with an aqueous solution of an alkali carbonate (hereinafter also referred to as aqueous solution (B)) is one of the preferred embodiments of the present invention. In the neutralization step, when the aqueous solution (A) and the aqueous solution (B) are mixed, the mixing method is not particularly limited, and the aqueous solution (B) may be added to the aqueous solution (A) or the aqueous solution (A) may be added to the aqueous solution (B), but it is preferable to simultaneously drop and mix the aqueous solutions (A) and (B) in small amounts. This further improves the dispersion degree of nickel in the obtained reduction catalyst precursor, and further improves the catalytic activity of the obtained reduction catalyst.

[0014] In the neutralization step, when the aqueous solution (A) is used, the concentration of nickel element in the aqueous solution (A) is preferably 0.05 to 2.0 mol / L, and more preferably 0.1 to 1.0 mol / L. The concentration of zirconium element in the aqueous solution (A) is preferably 0.05 to 2.0 mol / L, and more preferably 0.1 to 1.0 mol / L.

[0015] In the neutralization step, when the aqueous solution (B) is used, the concentration of the alkali carbonate in the aqueous solution (B) is preferably 0.5 mol / L or more, more preferably 1.0 mol / L or more, and is preferably 5 mol / L or less.

[0016] The nickel-containing compound used in the neutralization step is not particularly limited as long as it contains nickel element, but examples thereof include compounds such as sulfates, chlorides, oxides, hydroxides, acetates, carbonates, and basic carbonates, as well as metallic nickel, and one or more of these can be used. Among these, nickel sulfate and nickel chloride are preferred.

[0017] The zirconium-containing compound used in the neutralization step is not particularly limited as long as it contains zirconium element, and examples thereof include hydroxides, hydroxide oxides, chlorides, sulfides, sulfates, nitrates, carbonates, hydrogencarbonates, acetates, phosphates, oxalates, butyrates, selenates, iodates, fluorides, oxychlorides, and metallic zirconium, and one or more of these can be used. Among these, zirconium oxychloride and zirconium sulfate are preferred.

[0018] The alkali carbonate used in the neutralization step is not particularly limited as long as it is an alkali metal carbonate and / or hydrogen carbonate. The alkali metal includes lithium, sodium, potassium, rubidium, cesium, and francium, and is preferably lithium, sodium, or potassium, and more preferably sodium. Specific examples of the alkali carbonate include lithium carbonate, sodium carbonate, potassium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, and potassium hydrogen carbonate, with sodium carbonate and sodium hydrogen carbonate being preferred. When the alkali metal is sodium, the alkali metal can be easily removed after neutralization, and therefore the amount of the alkali metal remaining in the obtained reduction catalyst precursor can be more sufficiently reduced, and the activity of the obtained reduction catalyst is further improved. An embodiment in which the alkali carbonate is sodium carbonate and / or sodium hydrogen carbonate is one of the preferred embodiments of the present invention. The alkali carbonate is preferably a carbonate, which increases the specific surface area of ​​the resulting reduction catalyst precursor and reduction catalyst, thereby improving the catalytic activity.

[0019] The neutralization step is not particularly limited as long as it causes a neutralization reaction between the nickel-containing compound and the zirconium-containing compound and the alkali carbonate, but is characterized in that it is carried out in the presence of sulfate ions. When sulfate ions are used in the neutralization step, sulfates may be used as the nickel-containing compound and / or the zirconium-containing compound, or sulfate ions may be added separately from the nickel-containing compound or the zirconium-containing compound. When sulfate ions are added separately from the nickel-containing compound or the zirconium-containing compound, a sulfate of a metal element other than nickel or zirconium can be used, preferably an alkali metal or alkaline earth metal sulfate, more preferably an alkali metal sulfate, and even more preferably sodium sulfate.

[0020] The amount of sulfate ions used in the neutralization step is not particularly limited, but is preferably 10 to 200 mol % relative to 100 mol % in total of zirconium element and nickel element, more preferably 20 to 100 mol %, and further preferably 30 to 70 mol %.

[0021] In the neutralization step, the amount of nitrate ions used is preferably 1 mol % or less relative to 100 mol % of zirconium, which can reduce wastewater containing nitrate ions and is also excellent from the environmental point of view. The amount of nitrate ions used is more preferably 0.5 mol % or less, further preferably 0.1 mol % or less, and most preferably 0 mol %, relative to 100 mol % of zirconium.

[0022] The amounts of the nickel-containing compound and the zirconium-containing compound used in the neutralization step are not particularly limited, but the molar ratio of nickel element to zirconium element (nickel element / zirconium element) is preferably 0.1 to 20, more preferably 0.5 to 15, further preferably 1 to 10, and particularly preferably 1 to 5.

[0023] The amount of the alkali carbonate used in the neutralization step (equivalent amount of base) is not particularly limited, but is preferably 0.9 to 1.7 equivalents, more preferably 1.1 to 1.5 equivalents, per equivalent of the zirconium-containing compound and the nickel-containing compound in total.

[0024] In the neutralization step, components other than the nickel-containing compound, the zirconium-containing compound, the alkali carbonate, and the sulfate ions may be added, such as silicon-containing compounds, such as silica. In the above neutralization step, an embodiment in which a silicon-containing compound is further added is also one of the preferred embodiments of the present invention. In the neutralization step, the addition of a silicon-containing compound suppresses the particle growth of nickel and zirconium, thereby increasing the surface area, and the resulting reduction catalyst precursor has superior heat resistance, which allows the reduction catalyst to exhibit sufficient catalytic activity even at low temperatures and be usable over a wide range of temperatures. The silicon-containing compound is not particularly limited as long as it contains silicon element, and examples thereof include fine silica powder, silica sol, sodium silicate, etc., and one or more of these can be used. Among these, silica sol and sodium silicate are preferred, and sodium metasilicate is more preferred. When the silicon-containing compound is water-soluble such as sodium silicate, it can be added as an aqueous solution, so that the dispersibility is excellent, the surface area of ​​the obtained particles is further improved, and the heat resistance is excellent.

[0025] The amount of the silicon-containing compound added in terms of SiO2 is preferably 0.5 to 15 mass% relative to 100 mass% of the total of nickel element and zirconium element (total of nickel element in the nickel-containing compound and zirconium element in the zirconium-containing compound). More preferably, it is 1 to 10 mass%, and even more preferably, it is 1 to 5 mass%. In this specification, the amount of the silicon-containing compound in terms of SiO2 or an expression similar thereto means the amount of the silicon-containing compound when the silicon-containing compound is SiO2, and when the silicon-containing compound is a compound other than SiO2, it means a value obtained by multiplying the number of moles of silicon element in the compound by the molecular weight of SiO2.

[0026] The pH during the neutralization reaction in the neutralization step is not particularly limited, but is preferably 6.5 to 8.5. This improves the dispersibility of nickel in the resulting reduction catalyst precursor, and further improves the catalytic activity of the resulting reduction catalyst. The pH is more preferably 6.5 to 7.5. In the neutralization step, it is preferable to mix the aqueous solutions (A) and (B) dropwise so that the pH of the reaction solution becomes 6.5 to 8.5.

[0027] The reaction temperature in the neutralization step is not particularly limited, but is preferably 50° C. or higher. This increases the rate of the neutralization reaction and improves the dispersibility of nickel in the resulting reduction catalyst precursor. The reaction temperature is more preferably 50 to 80° C., and even more preferably 60 to 70° C.

[0028] The neutralization reaction time in the neutralization step is not particularly limited, but is preferably 0.5 to 8 hours, more preferably 1 to 6 hours, and further preferably 2 to 4 hours.

[0029] The method for producing the reduced catalyst precursor includes a step of filtering and washing the product obtained in the neutralization step to remove water-soluble components. The removal step is not particularly limited as long as the product obtained in the neutralization step can be filtered and washed with water to remove water-soluble components such as alkali metal ions and sulfate ions. The amount of water used in the above removal step is not particularly limited, but it is preferable to perform the removal step until the conductivity of the filtrate after washing with water becomes 100 mS / m or less, more preferably 50 mS / m or less, and even more preferably 20 mS / m or less.

[0030] The method for producing the reduced catalyst precursor includes a step of heat-treating the product obtained after the removal step. The heat treatment step is not particularly limited as long as the product is oxidized to obtain a reduced catalyst precursor that contains nickel oxide and zirconium oxide. The heat treatment step preferably includes a step of calcining the product after the removal step at a temperature of at least 500° C. The calcination temperature is more preferably 500 to 800° C., and further preferably 600 to 700° C.

[0031] In addition, the heat treatment step preferably includes a step of drying the product obtained after the removal step before the calcination. The drying temperature is not particularly limited, but is preferably 80 to 200° C. The drying temperature is more preferably 100 to 150° C.

[0032] The oxide obtained by the heat treatment step preferably has a Na2O content of 0.5 mass % or less, more preferably 0.2 mass % or less. Moreover, the oxide obtained by the above heat treatment step preferably has an SO3 content of 0.1 mass % or less, more preferably 0.05 mass % or less. If the contents of Na2O and SO3 are not more than the above-mentioned preferable amounts, the activity of the obtained reduction catalyst is further improved.

[0033] 2. Reduced Catalyst Precursor The present invention relates to a reduction catalyst precursor containing nickel oxide and zirconium oxide, the proportion of monoclinic zirconium oxide being 20% ​​by volume or less relative to 100% by volume of zirconium oxide, and the amount of CO adsorption after reduction treatment under the following conditions is 3 cm 3 / g or more. <Reduction treatment conditions> Amount of reduction catalyst precursor: 0.04g Gas type and flow rate: Hydrogen 50mL / min Temperature: 400℃ Reduction processing time: 30 minutes

[0034] The method for producing the reduced catalyst precursor of the present invention is not particularly limited, but it is preferable to produce it by the method for producing the reduced catalyst precursor of the present invention.

[0035] In the reduction catalyst precursor, the proportion of monoclinic zirconium oxide is preferably 20% by volume or less relative to 100% by volume of zirconium oxide, which further improves the activity of the resulting reduction catalyst. The proportion of monoclinic zirconium oxide is more preferably 15 vol % or less, further preferably 10 vol % or less, and particularly preferably 5 vol % or less. The reduction catalyst precursor may contain monoclinic zirconium oxide at a ratio of 20 volume % or less, but preferably contains tetragonal or cubic zirconium oxide, and more preferably contains tetragonal zirconium oxide. In the reduction catalyst precursor, the total ratio of tetragonal and cubic zirconium oxide is preferably 80% by volume or more relative to 100% by volume of zirconium oxide. An embodiment in which the ratio of tetragonal zirconium oxide is 80% by volume or more is one of the preferred embodiments of the present invention. The proportions of monoclinic, tetragonal and cubic crystals in the zirconium oxide can be measured by the method described in the Examples.

[0036] The reduction catalyst precursor contains nickel oxide and zirconium oxide, and the content ratio of the components is not particularly limited, but the ratio of nickel oxide is preferably 30 to 80 mass% relative to 100 mass% of the total of nickel oxide and zirconium oxide, more preferably 40 to 70 mass%, further preferably 45 to 70 mass%, and particularly preferably 50 to 70 mass%.

[0037] The reduction catalyst precursor may contain other components as long as it contains nickel oxide and zirconium oxide. The other components are not particularly limited, but include metallic nickel, metallic zirconium, and silicon-containing compounds such as silica. The content of the other components is not particularly limited, but is preferably 0 to 20 mass% relative to 100 mass% of the total of nickel oxide and zirconium oxide, more preferably 0 to 10 mass%, and even more preferably 0 to 1 mass%.

[0038] In one preferred embodiment of the present invention, the reduction catalyst precursor further contains a silicon-containing compound. Specific examples and preferred embodiments of the silicon-containing compound are as described above. By including a silicon-containing compound in the reduction catalyst precursor, the zirconium oxide in the catalyst is prevented from changing from a tetragonal crystal to a monoclinic crystal even when the catalyst is exposed to high temperatures of 700°C or higher, and activity at low temperatures is also improved.

[0039] The content ratio of the silicon-containing compound calculated as SiO2 is not particularly limited, but is preferably 0.5 to 15 mass% relative to 100 mass% of the total of nickel element and zirconium element in the reduction catalyst precursor, more preferably 1 to 10 mass%, and further preferably 1 to 5 mass%.

[0040] The reduction catalyst precursor had a CO adsorption capacity of 3 cm after reduction treatment under the above conditions. 3 / g or more. The CO adsorption capacity is 3 cm 3 / g or more, the degree of dispersion of nickel in the reduction catalyst precursor is sufficient, and the activity of the resulting reduction catalyst is further improved. There is no particular upper limit for the CO adsorption amount, but it is usually 5 cm 3 / g or less.

[0041] The reduction catalyst precursor has a specific surface area of ​​30 m 2 / g or more. This further improves the activity of the resulting reduction catalyst. The specific surface area is preferably 35 m 2 / g or more, more preferably 40m 2 / g or more, and particularly preferably 45m 2 / g or more. The specific surface area is usually 100 m 2 / g or less.

[0042] The reduction catalyst precursor preferably has a Na2O content of 0.5 mass % or less, more preferably 0.2 mass % or less. Moreover, the reduction catalyst precursor preferably has an SO3 content of 0.1 mass % or less, more preferably 0.05 mass % or less. If the contents of Na2O and SO3 are not more than the above-mentioned preferable amounts, the activity of the obtained reduction catalyst is further improved.

[0043] The reduction catalyst precursor has a pore volume of 0.1 cm 3 / g or more. This allows gas diffusion to proceed more sufficiently in the resulting reduction catalyst, and the activity is further improved. The pore volume is preferably 0.2 cm 3 / g or more, more preferably 0.3 cm 3 / g or more.

[0044] 3. Manufacturing method of reduction catalyst The present invention also provides a method for producing a reduction catalyst, the method including: a neutralization step of neutralizing a nickel-containing compound and a zirconium-containing compound with an alkali carbonate in the presence of sulfate ions; a step of removing water-soluble components from a product obtained in the neutralization step; a step of heat-treating the product after the removal step; and a step of reducing an oxide obtained by the heat-treatment step. The neutralization step, the water-soluble component removal step, and the heat treatment step in the above-mentioned production method for the reduced catalyst are as described above in the production method for the reduced catalyst precursor of the present invention.

[0045] The step of reducing the oxide obtained by the heat treatment step (hereinafter also referred to as the reduction step) is not particularly limited as long as it can reduce the nickel oxide contained in the oxide, but it is preferable to heat the oxide in a reducing atmosphere. The reducing gas used in the reduction step includes hydrogen, carbon monoxide, etc. The reducing gas is preferably hydrogen. In the reduction step, a mixed gas of the reducing gas and an inert gas such as nitrogen or argon may be used. The mixed gas preferably contains the reducing gas at a ratio of 10 to 100% by volume.

[0046] The reduction temperature in the reduction step is not particularly limited, but is preferably 200°C or higher, more preferably 300 to 500°C, and even more preferably 350 to 450°C.

[0047] The reduction treatment time in the reduction step is not particularly limited, but is preferably 1 to 12 hours, more preferably 2 to 8 hours, and further preferably 3 to 5 hours.

[0048] The method for producing the reduction catalyst preferably includes a step of oxidizing the surface of the product obtained in the reduction step, which further improves the stability of the reduction catalyst and makes it easier to handle. The oxidation step is not particularly limited as long as it oxidizes the surface of the product obtained in the reduction step, but it is preferable to oxidize the outermost surface of the product obtained in the reduction step.

[0049] The oxidation step is preferably performed in an oxidizing atmosphere. The oxidizing gas used in the oxidation step includes oxygen, water vapor, carbon dioxide gas, combustion gas, etc. The oxidizing gas is preferably oxygen gas. In the oxidation step, a mixed gas of the oxidizing gas and an inert gas such as nitrogen or argon may be used. The mixed gas preferably contains the oxidizing gas at a ratio of 0.1 to 20% by volume.

[0050] The oxidation treatment temperature in the oxidation step is not particularly limited, but is preferably 150° C. or lower, more preferably 120° C. or lower, and even more preferably 100° C. or lower.

[0051] The oxidation treatment time in the oxidation step is not particularly limited, but is preferably 1 to 12 hours, more preferably 2 to 8 hours, and further preferably 3 to 5 hours.

[0052] 4. Reduction catalyst The reduced catalyst precursor obtained by the method for producing a reduced catalyst precursor of the present invention can be suitably used as a reduced catalyst material, and a reduced catalyst can be obtained by reducing the reduced catalyst precursor. The present invention also includes a reduced catalyst, which is a reduction product of the above-mentioned reduced catalyst precursor. The preferred ranges of the Na2O content, SO3 content, silicon-containing compound content, CO adsorption amount, specific surface area, specific volume, and pore volume in the reduction catalyst are the same as those in the reduction catalyst precursor of the present invention. The reduction catalyst can be used as a catalyst for the reduction reaction of carbon dioxide, unsaturated hydrocarbons, etc., and can be suitably used for the reaction of reducing carbon dioxide to produce methane. An embodiment in which the reduction catalyst is a methanation catalyst is one of the preferred embodiments of the present invention.

[0053] The reduction catalyst of the present invention contains metallic nickel. The content of metallic nickel in the reduction catalyst is not particularly limited, but is preferably 10% by mass or more, more preferably 20% by mass or more, relative to 100% by mass of the reduction catalyst.

[0054] 5. How methane is produced The reduction catalyst of the present invention can be suitably used in a method for producing methane by reducing carbon dioxide. A method for producing methane, which includes a step of reducing carbon dioxide using the reduction catalyst of the present invention, also constitutes the present invention. The present invention is also a method for producing methane, comprising the steps of preparing a methanation catalyst and reducing carbon dioxide using the methanation catalyst obtained in the preparation step, the preparation step comprising a neutralization step of neutralizing a nickel-containing compound and a zirconium-containing compound with an alkali carbonate in the presence of sulfate ions, a step of removing water-soluble components from the product obtained in the neutralization step, a step of heat-treating the product after the removal step, and a step of reducing the oxide obtained by the heat-treatment step. The neutralization step, the water-soluble component removal step, the heat treatment step, and the reduction step in the above-mentioned method for producing methane are as described in the method for producing a reduced catalyst precursor and the method for producing a reduced catalyst of the present invention. EXAMPLES

[0055] In order to explain the present invention in detail, specific examples are given below, but the present invention is not limited to these examples. The methods for measuring each physical property are as follows.

[0056] <Evaluation of carbon dioxide methanation activity> The reduction catalyst precursors obtained in the examples and comparative examples were passed through sieves with an aperture of 1.18 mm and 0.85 mm, and the granules (1.18 - 0.85 mm) in the sieves were collected to obtain samples for evaluating the methanation activity of carbon dioxide. 1.00 g of the sample was fixed in the center of a quartz glass tube with a diameter of 1.8 cm and a length of 45 cm and set in a tubular electric furnace. Hydrogen was passed through the quartz glass tube at a rate of 400 mL / min under normal pressure. After heating up to 400 °C, it was held for 3 hours for reduction treatment. After the reduction treatment, while hydrogen was still flowing, the temperature was lowered to room temperature, and then a mixed gas of 750 mL / min of nitrogen, 200 mL / min of hydrogen, and 50 mL / min of carbon dioxide was passed through. It was heated up from 100 °C, and the generated gas during the holding at each temperature was analyzed by gas chromatography, and the carbon dioxide conversion rate was calculated from the following formula. Carbon dioxide conversion rate (%) = (inlet carbon dioxide amount - outlet carbon dioxide amount) × 100 / inlet carbon dioxide amount

[0057] <Measurement of the content of each component> The measurement of the content of the components contained in the reduction catalyst precursor was carried out using a scanning fluorescent X-ray analyzer ZSX PrimusII manufactured by Rigaku Corporation.

[0058] <Measurement of specific surface area> The specific surface area was measured by the BET method using BELSORP-mini manufactured by MicrotracBEL Corp.

[0059] <Measurement of pore volume> The pore volume was measured by the N2 adsorption method using BELSORP-mini manufactured by MicrotracBEL Corp.

[0060] <Measurement of CO adsorption amount> The CO adsorption amount was measured by the CO pulse method using BELCAT-II manufactured by MicrotracBEL Corp. He was used as the carrier gas, and the composition of the adsorbed gas was 10 vol% of CO and 90 vol% of He. Amount of reduction catalyst precursor: 0.04 g Type and rate of gas: 50 mL / min of hydrogen Temperature: 400 °C Reduction treatment time: 30 minutes CO adsorption temperature: 50℃

[0061] <Evaluation of crystal structure> The crystal structure of zirconium oxide was evaluated by powder X-ray diffraction using a Bruker D8 ADVANCE X-ray diffractometer, and the proportion (volume %) of monoclinic crystals contained in zirconium oxide was calculated using the following Toraya formula.

[0062]

number

number

[0063] <Evaluation of heat resistance> The granular reduction catalyst precursor was heat-treated in an electric furnace in air at 700°C for 50 hours, and then its carbon dioxide methanation activity was evaluated.

[0064] <Example 1> 104.5g of nickel (II) sulfate hexahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 100.0g of zirconium chloride octahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were dissolved in 690mL of ion-exchanged water. 100.0g of sodium carbonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was dissolved in 500mL of ion-exchanged water. 300mL of ion-exchanged water was placed in a 2L glass beaker, heated and maintained at 70°C, and the nickel-zirconium solution was dropped over 2 hours while stirring. At the same time, sodium carbonate solution was dropped and the pH was controlled to be within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered and washed with water until the conductivity of the filtrate was 20mS / m or less to remove sodium ions and sulfate ions, and then the precipitate was dried at 110°C overnight and calcined at 650°C to obtain the reduction catalyst precursor of Example 1.

[0065] <Example 2> 104.5 g of nickel (II) sulfate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 100.0 g of zirconium chloride octahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 390 mL of ion-exchanged water. 158.0 g of sodium hydrogen carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed in a 2 L glass beaker and dissolved in 1100 mL of ion-exchanged water. The aqueous sodium hydrogen carbonate solution was heated and held at 70°C, and the nickel-zirconium solution was added dropwise over 2 hours while stirring. At this time, the pH at the beginning of the reaction was 8.15, and the pH at the end of the reaction was 6.50. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110°C overnight and calcined at 650°C for 5 hours to obtain the reduction catalyst precursor of Example 2.

[0066] <Example 3> 104.5 g of nickel (II) sulfate hexahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 100.0 g of zirconium chloride octahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were dissolved in 400 mL of ion-exchanged water. 178.0 g of sodium hydrogen carbonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was dissolved in 1800 mL of ion-exchanged water. 500 mL of ion-exchanged water was placed in a 3 L glass beaker, heated and maintained at 70 ° C., and the nickel-zirconium solution was dropped over 2 hours while stirring. At the same time, sodium hydrogen carbonate solution was dropped to control the pH to be within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110 ° C. overnight and calcined at 650 ° C. for 5 hours to obtain the reduction catalyst precursor of Example 3.

[0067] <Example 4> 94.5g of nickel (II) chloride hexahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 100.0g of zirconium chloride octahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 50.0g of sodium sulfate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were dissolved in 680mL of ion-exchanged water. 100.0g of sodium carbonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was dissolved in 500mL of ion-exchanged water. 300mL of ion-exchanged water was placed in a 2L glass beaker, heated and maintained at 70°C, and the nickel-zirconium solution was added dropwise over 2 hours while stirring. At the same time, a sodium carbonate solution was added dropwise to control the pH to within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110°C overnight and calcined at 650°C for 5 hours to obtain the reduction catalyst precursor of Example 4.

[0068] <Example 5> 155.5 g of nickel (II) sulfate hexahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 62.2 g of zirconium chloride octahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were dissolved in 690 mL of ion-exchanged water. 100.0 g of sodium carbonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was dissolved in 500 mL of ion-exchanged water. 300 mL of ion-exchanged water was placed in a 2 L glass beaker, heated and maintained at 70 ° C., and the nickel-zirconium solution was dropped over 2 hours while stirring. At the same time, sodium carbonate solution was dropped to control the pH to be within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110 ° C. overnight and calcined at 650 ° C. to obtain the reduction catalyst precursor of Example 5.

[0069] <Example 6> 152.4 g of nickel (II) sulfate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 61.0 g of zirconium chloride octahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 680 ml of ion-exchanged water, and 6.8 g of silica sol (Nissan Chemical Snowtex-O) was added. 100.0 g of sodium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 500 ml of ion-exchanged water. 300 ml of ion-exchanged water was placed in a 2 L glass beaker, heated and maintained at 70 ° C., and the nickel-zirconium-silica solution was dropped over 2 hours while stirring. At the same time, sodium carbonate solution was dropped to control the pH to within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110 ° C. overnight and calcined at 650 ° C. to obtain the reduction catalyst precursor of Example 6.

[0070] <Example 7> 151.6 g of nickel (II) sulfate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 60.7 g of zirconium chloride octahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 600 mL of ion-exchanged water. 6.0 g of sodium metasilicate pentahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 100 mL of ion-exchanged water. 145.0 g of sodium hydrogen carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was taken in a 2 L glass beaker and dissolved in 900 mL of ion-exchanged water. The aqueous sodium hydrogen carbonate solution was heated and held at 70 ° C., and while stirring, the nickel-zirconium solution and the sodium metasilicate solution were simultaneously dropped over 2 hours. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110 ° C. overnight and calcined at 650 ° C. for 5 hours to obtain the reduction catalyst precursor of Example 7.

[0071] <Comparative Example 1> 94.5g of nickel (II) chloride hexahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 100.0g of zirconium chloride oxide (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were dissolved in 690mL of ion-exchanged water. 100.0g of sodium carbonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was dissolved in 500mL of ion-exchanged water. 300ml of ion-exchanged water was placed in a 2L glass beaker, heated and maintained at 70°C, and the nickel-zirconium solution and the sodium carbonate solution were simultaneously dropped while stirring. At this time, the dropping speed of both solutions was controlled so that the pH was within the range of 6.5 to 7.5. The obtained precipitate was filtered and washed with water, and then the precipitate was dried at 110°C overnight and calcined at 650°C to obtain a comparative reduction catalyst precursor of Comparative Example 1.

[0072] <Comparative Example 2> 104.5g of nickel (II) sulfate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 100.0g of zirconium chloride octahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 690mL of ion-exchanged water. 52.8g of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 200mL of ion-exchanged water. 300mL of ion-exchanged water was placed in a 2L glass beaker and heated to 70°C. The nickel-zirconium solution was added dropwise over 2 hours while stirring. At the same time, sodium hydroxide solution was added dropwise to control the pH to within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110°C overnight and calcined at 650°C for 5 hours to obtain a comparative reduction catalyst precursor of Comparative Example 2.

[0073] <Comparative Example 3> 104.5 g of nickel (II) sulfate hexahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and 100.0 g of zirconium chloride octahydrate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were dissolved in 690 mL of ion-exchanged water. 100.0 g of 28 mass% ammonia water (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) was diluted with 100 mL of ion-exchanged water. 300 mL of ion-exchanged water was placed in a 2 L glass beaker, heated and maintained at 70 ° C., and the nickel-zirconium solution was dropped over 2 hours while stirring. At the same time, an aqueous ammonia solution was dropped to control the pH to within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110 ° C. overnight and calcined at 650 ° C. for 5 hours to obtain a comparative reduction catalyst precursor of Comparative Example 3.

[0074] <Comparative Example 4> 115.6 g of nickel (II) nitrate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 100.0 g of zirconium chloride octahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 680 mL of ion-exchanged water. 52.8 g of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 200 mL of ion-exchanged water. 300 mL of ion-exchanged water was placed in a 2 L glass beaker and heated to 70 ° C., and the nickel-zirconium solution was dropped over 2 hours while stirring. At the same time, sodium hydroxide solution was dropped to control the pH to within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered and washed with water, and then the precipitate was dried at 110 ° C. overnight and calcined at 650 ° C. for 5 hours to obtain a comparative reduction catalyst precursor of Comparative Example 4.

[0075] <Comparative Example 5> 104.5g of nickel (II) sulfate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 100.0g of zirconium chloride octahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 690mL of ion-exchanged water. 100.0g of sodium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 500mL of ion-exchanged water. 300mL of ion-exchanged water was placed in a 2L glass beaker, heated and maintained at 70°C, and the nickel-zirconium solution was dropped over 2 hours while stirring. At the same time, sodium carbonate solution was dropped and the pH was controlled to be within the range of 6.5 to 7.5. The precipitate obtained by the neutralization reaction was filtered, and washing was stopped when the conductivity of the filtrate was 160mS / m, and the precipitate was dried at 110°C overnight and calcined at 650°C for 5 hours to obtain a comparative reduction catalyst precursor of Comparative Example 5.

[0076] <Comparative Example 6> 34.3 g of nickel (II) nitrate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 30 mL of ion-exchanged water. 56.0 g of zirconia sol (ZSL-20N manufactured by Daiichi Kigenso Kagaku Co., Ltd.) was added thereto and thoroughly mixed. The obtained slurry was transferred to a crucible and fired at 650°C for 5 hours to obtain a comparative reduction catalyst precursor of Comparative Example 6.

[0077] <Comparative Example 7> 34.3 g of nickel (II) nitrate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 4.08 g of samarium nitrate hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were dissolved in 30 mL of ion-exchanged water. 48.0 g of zirconia sol (ZSL-20N manufactured by Daiichi Kigenso Kagaku Co., Ltd.) was added thereto and thoroughly mixed. The obtained slurry was transferred to a crucible and fired at 650°C for 5 hours to obtain a catalyst precursor of Comparative Example 7.

[0078] Various physical properties of the reduction catalyst precursors obtained in the examples and comparative examples are shown in Tables 1 and 2.

[0079] [Table 1]

[0080] [Table 2]

[0081] As shown in Table 1, by performing the neutralization step in the presence of sulfate ions, the pore volume and CO adsorption amount are improved, and the CO2 conversion rate is improved, compared to when sulfate ions are not used (Comparative Example 1). In addition, by using an alkali carbonate as a base, the SO3 content in the oxide obtained by the heat treatment step is 0.5 mass% or less, and the CO2 conversion rate is improved, compared to when sodium hydroxide or ammonia is used as a base (Comparative Examples 2 and 3). Furthermore, by thoroughly washing with water so that the Na2O content in the oxide obtained by the heat treatment step is 1.0 mass% or less, a reduction catalyst precursor having a high CO2 conversion rate can be obtained compared to the case where the Na2O content exceeds 1.0 mass% (Comparative Example 5). Furthermore, in Comparative Example 7, by using Sm as a stabilizer, a higher CO2 conversion rate is obtained compared to Comparative Example 6, which does not use a stabilizer, but NOx is generated by calcining using nickel nitrate. In contrast, it was confirmed that the production method of the reduction catalyst precursor of the present invention does not use a stabilizer such as a rare earth element, does not generate a large amount of NOx during calcination, and can obtain a reduction catalyst precursor that shows activity equal to or higher than that of Comparative Example 7. Furthermore, as shown in Table 2, it was confirmed that the reduction catalyst precursor contained a silicon-containing compound, which prevented the zirconium oxide in the catalyst from changing from a tetragonal crystal to a monoclinic crystal even when the catalyst was exposed to a high temperature of 700°C or higher, and improved activity at a low temperature of 250°C (Examples 6 and 7).

Claims

1. 1. A method for producing a reduced catalyst precursor, comprising the steps of: The production method includes a neutralization step of neutralizing a nickel-containing compound, a zirconium-containing compound, and an alkali carbonate in the presence of sulfate ions; a step of filtering and washing the product obtained in the neutralization step to remove water-soluble components; and a step of heat treating the product after the removing step, Na in the oxide obtained by the heat treatment process 2 The content of O is 1.0 mass% or less, and SO 3 The method for producing a reduced catalyst precursor, wherein the content of is 0.5 mass% or less.

2. The method for producing a reduced catalyst precursor according to claim 1 , wherein in the neutralization step, an aqueous solution containing a nickel-containing compound and a zirconium-containing compound is mixed with an aqueous solution of an alkali carbonate.

3. The method for producing a reduced catalyst precursor according to claim 1 , wherein a silicon-containing compound is further added in the neutralization step.

4. The silicon-containing compound SiO 2 The method for producing a reduced catalyst precursor according to claim 1, wherein the amount of addition calculated as the amount of nickel and zirconium is 0.5 to 15 mass% relative to 100 mass% in total.

5. The method for producing a reduced catalyst precursor according to claim 1, wherein the alkali carbonate is sodium carbonate and / or sodium hydrogen carbonate.

6. The method for producing a reduced catalyst precursor according to claim 1, wherein the pH during the neutralization reaction in the neutralization step is 6.5 to 8.

5.

7. The method for producing a reduced catalyst precursor according to claim 1, wherein the reaction temperature in the neutralization step is 50° C. or higher.

8. The method for producing a reduced catalyst precursor according to claim 1, comprising a neutralization step, a water-soluble component removal step, and a heat treatment step, Further, the method includes a step of reducing the oxide obtained by the heat treatment step, Na in the oxide obtained by the heat treatment process 2 The content of O is 1.0 mass% or less, and SO 3 The method for producing a reduction catalyst, wherein the content of is 0.5 mass% or less.

9. The method for producing a reduced catalyst according to claim 8, further comprising a step of oxidizing a surface of the product obtained in the reduction step.

10. The method for producing a reduction catalyst according to claim 8 or 9, wherein the reduction catalyst is a methanation catalyst.

11. A reduction catalyst precursor comprising nickel oxide and zirconium oxide, The reduction catalyst precursor has a monoclinic zirconium oxide ratio of 20% by volume or less relative to 100% by volume of zirconium oxide, and has a CO adsorption capacity of 3 cm3 after reduction treatment under the following conditions: 3 / g or more. <Reduction Treatment Conditions> Amount of reduced catalyst precursor: 0.04 g Gas type and flow rate: Hydrogen 50 mL / min Temperature: 400℃ Reduction treatment time: 30 minutes

12. The reduced catalyst precursor of claim 11 , wherein the reduced catalyst precursor further comprises a silicon-containing compound.

13. The silicon-containing compound SiO 2 The reduction catalyst precursor according to claim 11, wherein the content ratio calculated based on the total amount of nickel element and zirconium element in the reduction catalyst precursor is 0.5 to 15 mass% based on 100 mass%.

14. Specific surface area is 30m 2 / g or more.

15. A reduced catalyst which is a reduction product of the reduced catalyst precursor according to claim 11.

16. 16. The reduction catalyst of claim 15 which is a methanation catalyst.

17. A method for producing methane, comprising a step of reducing carbon dioxide using the reduction catalyst according to claim 16.

Citation Information

Patent Citations

  • Carbon monoxide methanating catalyst and preparation method thereof

    CN103480375A

  • Metankoganryogasuseizoyono shokubai

    JP1976025493A

  • Preparation of a coprecipitated nickel-zirconium catalyst

    US2564331A

  • CATALYTIC MATERIAL COMPRISING Ni SUPPORTED ON AN OXIDIC SUPPORT COMPRISING Zr AND Si

    WO2021219796A1

  • Catalyst for methanizing carbon dioxide

    JP2000254508A